2007
DOI: 10.1007/s12070-007-0097-z
|View full text |Cite
|
Sign up to set email alerts
|

Adult tonsillectomy and day care surgery

Abstract: Objective To evaluate the safety of adult tonsillectomy as a day care surgery Methods Records of 664 patients above the age of 12 years, who underwent tonsillectomy were analysed. These patients were operated in our department within January 1999 and September 2002. Only 13 patients (1.95%) had post operative bleeding and were readmitted after discharge. The data of these patients were collected from medical records as well from the morbidity meeting proceedings and was reviewed retrospectively. Statistical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…References revealed two additional potentially relevant studies. 67,68 Studies were excluded for the following reasons: only posttonsillectomy data was available, 24 no polysomnography or quantitative sleepiness data, 20,29,34,38,44,48,56,57,[60][61][62]64,65 the patient(s) underwent a tonsillectomy alone; however, the studies only reported data for the entire group which included additional surgeries, 28,41,[50][51][52][53] the patient(s) underwent another procedure simultaneously, 10,22,27,42,45,46,55,58,67,69 or the articles were review articles with no new data. 23,30 Seventeen studies 21,25,26,[31][32][33][35][36][37]39,40,42,49,54,<...>…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…References revealed two additional potentially relevant studies. 67,68 Studies were excluded for the following reasons: only posttonsillectomy data was available, 24 no polysomnography or quantitative sleepiness data, 20,29,34,38,44,48,56,57,[60][61][62]64,65 the patient(s) underwent a tonsillectomy alone; however, the studies only reported data for the entire group which included additional surgeries, 28,41,[50][51][52][53] the patient(s) underwent another procedure simultaneously, 10,22,27,42,45,46,55,58,67,69 or the articles were review articles with no new data. 23,30 Seventeen studies 21,25,26,[31][32][33][35][36][37]39,40,42,49,54,<...>…”
Section: Resultsmentioning
confidence: 99%
“…The searches yielded 2,318 studies: 47 were potentially relevant and were downloaded. References revealed two additional potentially relevant studies .…”
Section: Resultsmentioning
confidence: 99%